Carrier dynamics in polymer nanofiber : fullerene solar cells - Kurniawan, Michael (2012)
Organic photovoltaic (OPV) devices fabricated with P3HT nanofiber (NF) networks typically exhibit poorer device performance compared to their nanoscale phase separated P3HT:PCBM counterparts despite possessing superior light harvesting properties and high in-plane charge mobility. Herein, we investigate the charge generation and recombination dynamics in P3HT-NF:PCBM blend films using transient absorption spectroscopy (TAS) spanning a wide temporal range over 7 orders of magnitude (i.e., from 100 fs to 1 μs), which are correlated with device performance studies. TAS reveals a more efficient charge generation and polaron formation rate in the NF samples as compared to the control samples at the onset which persists up to 2 ns. However, within the nanoseconds to microseconds time scale, there is a significant amount of nongeminate recombination in the NF system. We attribute this to the poor interfibrillar charge transport between the NFs, which tend to align parallel to the electrodes, thereby causing charge localization. These charge dynamics were validated using the analytical model proposed by Laquai and co-workers [Howard, I. A.; et al. J. Am. Chem. Soc.2010, 132, 14866]. Importantly, our findings provide new insights into the factors that limit the photovoltaic performance of such P3HT-NF based devices.